Effectiveness of Project Based Learning Low Carbon STEM and Discovery Learning to Improve Creative Thinking Skills - Dyah Pramesti; Riezky Maya Probosari; Nurma Yunita Indriyanti (Journal of Innovation in Educational and Cultural Research, 2022)
Integrating low-carbon or environmentally friendly principles into the learning process is possible, especially in the Project-Based Learning-Science Technological Engineering and Mathematics (PjBL-STEM) model. This study aims to determine the difference in effectiveness between PjBL-Low Carbon STEM and discovery learning to develop the creative thinking abilities of class IX students at one of Surakarta's public junior high schools and educate them about electricity and to know the application of the low carbon concept. This research is a quasi-experimental research type. The research design used in this study is the Pretest-Posttest Control Group Design, where the experimental class applies PjBL-Low Carbon STEM, and the control class applies discovery learning. The population in this study were all grade IX students. The sample in this study was class IX A as the experimental class and class IX B as the control class. The sampling technique used random cluster sampling. The data collection technique used a test of creative thinking skills description and student response questionnaires. The hypothesis test used is the t-test (t-test). This study concludes that there are differences in the effectiveness of PjBL-Low Carbon STEM and discovery learning to improve the creative thinking skills of class IX students on electrical materials. Applying the low carbon concept in the learning process can improve students' understanding of common carbon principles, concepts, and attitudes.